Whether mismatch finds match in the digitalized era: A comparison of five types of graduates to align business education and banking jobs - Rahman, Md Mahfuzur; Alam, Gazi Mahabubul; Abdul Aziz, Nor Azni; Bashir, Karima; Kader, Romana (SAGE Publications Ltd, 2024)
Reasons for the emerging mismatch between education and the labor market, its impact and the resolving mechanisms have been well studied. However, mismatch continues to be very problematic. Moreover, the new era of digitalization and artificial intelligence is accelerating this crisis. Acknowledging this tenet, we investigate further—whether a mismatch finds a match in the digitalized era. An individualist approach to answer each research question was considered so descriptive statistics, multinomial logistic regression and interviews are adopted under were implemented using the framework of both quantitative and qualitative methods. Findings suggest that the overall performance of the fully mismatched group (Science graduates) is comprehensively better compared to their counterpart (Business graduates). Digitalization has further generated a mismatch since business graduates are now increasingly irrelevant. This paper supplements the discourse on education and job market mismatch by using a distinct measurement strategy. We argue that digitalized skills are now the required competence to do jobs in any sector. Hence, all types of schools (business, science, social sciences) should equip their graduates with digitized skills in order to prevent them being replaced by science graduates.